Neurofibromatosis Type 2 Presenting with Ptosis (TAJ: Journal of Teachers Association, 2009)
Neurofibromatosis type 2 (NF 2), formerly called bilateral Acoustic Neurofibromatosis, is a distinct disease, which must be separated clinically and radiologically from Neurofibromatosis type 1. We presented a case of NF 2 of 20-year-old female presented with a rare symptom, rightsided ptosis due to superior rectus muscle paresis, multiple subcutaneous nodules and hearing impairment. doi: 10.3329/taj.v21i2.3801 TAJ 2008; 21(2): 174-176